Randomized Comparison of Ridaforolimus- and Zotarolimus-Eluting Coronary Stents in Patients With Coronary Artery Disease: Primary Results From the BIONICS Trial (BioNIR Ridaforolimus-Eluting Coronary Stent System in Coronary Stenosis). Issue 14 (3rd October 2017) - Kandzari, David E.; Smits, Pieter C.; Love, Michael P.; Ben-Yehuda, Ori; Banai, Shmuel; Robinson, Simon D.; Jonas, Michael; Kornowski, Ran; Bagur, Rodrigo; Iniguez, Andres; Danenberg, Haim; Feldman, Robert; et al.
Abstract : Background: The safety and efficacy of a novel cobalt alloy-based coronary stent with a durable elastomeric polymer eluting the antiproliferative agent ridaforolimus for treatment of patients with coronary artery disease is undetermined. Methods: A prospective, international 1:1 randomized trial was conducted to evaluate in a noninferiority design the relative safety and efficacy of ridaforolimus-eluting stents (RESs) and slow-release zotarolimus-eluting stents among 1919 patients undergoing percutaneous coronary intervention at 76 centers. Inclusion criteria allowed enrollment of patients with recent myocardial infarction, total occlusions, bifurcations lesions, and other complex conditions. Results: Baseline clinical and angiographic characteristics were similar between the groups. Overall, mean age was 63.4 years, 32.5% had diabetes mellitus, and 39.7% presented with acute coronary syndromes. At 12 months, the primary end point of target lesion failure (composite of cardiac death, target vessel-related myocardial infarction, and target lesion revascularization) was 5.4% for both devices (upper bound of 1-sided 95% confidence interval 1.8%, P noninferiority =0.001). Definite/probable stent thrombosis rates were low in both groups (0.4% RES versus 0.6% zotarolimus-eluting stent, P =0.75); 13-month angiographic in-stent late lumen loss was 0.22±0.41 mm and 0.23±0.39 mm ( P noninferiority =0.004) for the RES and zotarolimus-eluting stent groups, respectively, and intravascular ultrasound percent neointimal hyperplasia was 8.10±5.81 and 8.85±7.77, respectively ( P noninferiority =0.01). Conclusions: In the present trial, which allowed broad inclusion criteria, the novel RESs met the prespecified criteria for noninferiority compared with zotarolimus-eluting stents for the primary end point of target lesion failure at 12 months and had similar measures of late lumen loss. These findings support the safety and efficacy of RESs in patients who are representative of clinical practice. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01995487. Abstract : Supplemental Digital Content is available in the text.